The effect of cross-over frequency on binaural hearing performance of adults using electric-acoustic stimulation. (4th July 2019) - Incerti, Paola V; Ching, Teresa YC; Cowan, Robert
Abstract : Objective : To investigate the effect of varying cross-over frequency (CF) settings for electric-acoustic (EA) stimulation in one ear combined with acoustic (A) hearing in the opposite ear on binaural speech perception, localization and functional performance in real life. Methods: Performance with three different CF settings set according to audiometric-based criterion were compared, following a four week familiarisation period with each, in ten adult cochlear implant recipients with residual hearing in both ears. On completion of all trials participants selected their preferred CF setting. Results: On average, CF settings did not have a significant effect on performance scores. However, higher ratings on device usage were associated with the preferred CF settings. Conclusion: Individuals who use EA + A stimulation may benefit from access to different CF settings to achieve maximal device usage.